Skills required by new chemistry graduates and their development in degree programmes - Hanson, Steve; Overton, Tina (The University of Hull)
This report is based on surveys of graduates from universities in England, Scotland and Wales, designed to identify which areas of the curriculum and generic skills are of particular value to new graduates and how well they were developed within the degrees.